H3F3A‐mutated giant cell tumour of bone without giant cells—clinical presentation, radiology and histology of three cases. Issue 5 (21st July 2021) - Leinauer, Benedikt; Wolf, Eduard; Werner, Mathias; Baumhoer, Daniel; Breining, Thomas; Luebke, Andreas M; Maas, Rainer; Schultheiß, Markus; von Baer, Alexandra; Sufi‐Siavach, Anusch; Moritz, Christian; Geißler, Sven; et al.
Abstract : Aims: Giant cell tumour of bone (GCTB) is histologically defined as a lesion containing reactive giant cells and a neoplastic mononuclear cell population; in up to 92% of cases, GCTB is characterised by a specific mutation of the histone gene H3F3A . The cellular composition ranges from giant‐cell‐rich to giant‐cell‐poor. The diagnosis of GCTB can be challenging, and several other lesions need to be excluded, e.g. aneurysmal bone cysts, non‐ossifying fibromas, chondroblastomas, brown tumours, and giant‐cell‐rich osteosarcomas. Our aim was to analyse the clinical history, imaging, molecular pathology and histology of three H3F3A ‐mutated bone tumours without detectable giant cells. None of the patients received denosumab therapy. Methods and results: Diagnostic material was obtained by curettage or resection and/or biopsy. Common histomorphological features of all three reported lesions were fibrocytic, oval cells in a background of osteoid and an absence of multinuclear giant cells as confirmed with CD68 immunohistochemistry. We used immunohistochemistry and Sanger sequencing to demonstrate positivity for the H3.3 p.G34W mutation. Differential diagnoses were systematically excluded on the basis of histomorphology, immunohistochemistry, and fluorescence in‐situ hybridisation. The imaging (radiography, computed tomography, and magnetic resonance imaging) for all three cases is presented and discussed. Conclusions: We believe that these GCTBs without giant cells expand one end of the heterogeneous range of GCTB. Because of the lack of giant cells, correct diagnosis of GCTB is challenging or even impossible on histological grounds alone. In these cases, detection of the characteristic H3F3A mutation (G34W‐specific antibody RM263 or sequencing) is extremely helpful for diagnosing those lesions without giant cells as giant cell tumours of bone. Abstract :